Bright past, shady future? Past and potential future export performance of CEE countries in a comparative perspective - Joéze Damijan; éCrt Kostevc; Matija Rojec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
In this paper we examine the reasons behind the remarkable export performance of transition economies in the last two decades. Following Redding and Venables (2004, 2004a) and Fugazza (2004), we decompose export performance into the gains due to the advantageous access to foreign markets and export gains on the side of the internal supply capacity. We find that size of the economy, inward FDI penetration, most notably in the manufacturing sector, export unit values, denoting the structural changes of CEECs' exports, and the quality of institutions and infrastructure had signi.cant positive impact on exporting country's supply capacity, while productivity had a negative impact. The latter is mostly due to unfavourable trends in ULC since the accession. Unlike in EU-15 and BRIC countries, the internal supply capacity is becoming decreasingly important as base of CEECs export performance. At the same time, trends in cost competitiveness are worsening relative to competing countries, while bene.ts of EU accession have been mostly exploited. This may compromise the CEECs.future export growth.
Keywords: F120; F150; F210; O100; P300; 330; exports performance; supply capacity; foreign market access; Central and Eastern European countries; Export; Markteintritt; Osteuropa